A Nephrotic Syndrome-specific Quality of Life Scale: Development Based on the Quality of Life Instruments for Chronic Diseases, and Verification Using the Classical Test Theory - ZHANG Xingshan, LIN Yue, WAN Chonghua, SONG Aifeng, PAN Haiyan (Zhongguo quanke yixue, 2023)
Background The quality of life of patients with nephrotic syndrome requires a lot of focus, and improvements. A relevant scale can be used to measure it, but there is no nephrotic syndrome-specific quality of scale. Objective To develop a Quality of Life Instruments for Chronic Diseases-Nephrotic Syndrome〔QLICD-NS (V2.0) 〕 combined with QLICD-GM (V2.0), then verify it using the classical test theory. Methods From 2017 to 2021, an item pool was established according to literature review and the results of a semi-structured questionnaire, then the items were screened in accordance with a pre-test and importance score rated by physicians and patients, after that, the draft of the QLICD-NS (V2.0) was developed. The draft version was tested using onsite interview and questionnaire survey in nephrotic syndrome patients treated in Department of Nephrology, the Affiliated Hospital of Guangdong Medical University from March to November 2021. The first measurement was conducted on the day of admission, the second measurement was conducted with some of the patients, and the third measurement was conducted on the day of discharge. The coefficient of variation, correlation coefficient and Cronbach's α, factor analysis and classical test theory were used to evaluate QLICD-NS (V2.0) . Results The QLICD-NS (V2.0) contains 15 items, belonging to three domains of clinical symptoms, adverse drug reactions and psychological effects. The Cronbach's α measuring the split-half reliability was greater than 0.7 for the scale and each of the three domains. With the Chinese version of SF-36 as the calibration standard, the domains of the QLICD-NS (V2.0) were highly correlated with their counterpart domains of the Chinese version of SF-36. The standardized response mean was greater than 0.80 for all domains and items (except for the cognition and social support items), indicating that the responsiveness of the QLICD-NS (V2.0) was good. Scanning the QR code in the text can obtain the detailed evaluation of the scale. Conclusion The QLICD-NS (V2.0) compiled by us includes 15 items, and has proven with good reliability, validity and responsiveness.